INFLUENCE OF PRODUCT QUALITY, BRAND TRUST, AND BRAND IDENTITY ON PRODUCT PURCHASE DECISION VENTELA SHOES - Hafidz, Muhammad Respati; D, Dian Komarsyah; M.Si, Fenny Saptiani (Jurnal Kompetitif Bisnis, 2022)
Abstract This study aims to determine the effect of product quality, brand trust, and brand identity on the decision to purchase Ventela shoes. This type of research is associative with a quantitative approach. The population used is students and students who have used Ventela brand shoes and have made at least one purchase. The data was obtained from a questionnaire filled out online, the sample was drawn using non-probability sampling with purposive sampling technique with a sample of 100 respondents. Data analysis used descriptive statistical analysis and classical assumption test with SPSS 26 application tools. Based on the results of the t test (partial) it showed that the variables of product quality, brand trust, and brand identity each had a significant effect on purchasing decisions. The results of the F (simultaneous) test explain that product quality, brand trust, and brand identity together have a significant effect on purchasing decisions. Then the R2 test shows that 42.1% of purchasing decisions are influenced by product quality, brand trust, and brand identity and the remaining 57.9% of purchasing decisions are influenced by other variables. Keywords: Product Quality, Brand Trust, Brand Identity, Purchase Decision